Adequacy of criminal legislation concerning the money laundering for cybercrimes in Mainland China - Chenghao, Yu; Zahir, Mohd Zamre Mohd; Rajamanickam, Ramalinggam (Edelweiss Applied Science and Technology, 2025)
This article examines the rising trend of cybercrime-related money laundering in Mainland China since 2020, focusing on challenges posed by legal ambiguities in enforcement. By comparing Mainland China’s legal framework with Taiwan’s recent legislative reforms, the study aims to provide recommendations for improving Mainland China’s criminal legislation to ensure consistent legal application and strengthen anti-money laundering efforts. Utilizing a qualitative methodology, this research combines analytical and comparative legal approaches. It analyzes relevant criminal laws, judicial interpretations, and enforcement practices in Mainland China and Taiwan, with a particular focus on legislative amendments made by Taiwan in 2023 and 2024. The study reveals that ambiguous legal definitions in Mainland China's Criminal Law and judicial interpretations have led to inconsistent enforcement and difficulties in effectively combating money laundering related to cybercrimes. In contrast, Taiwan’s proactive amendments demonstrate the benefits of precise legal provisions and comprehensive regulations. To enhance legal certainty, Mainland China should revise its laws to include explicit provisions on cybercrime-related money laundering and align enforcement mechanisms with international best practices. These recommendations can improve Mainland China’s legal framework, ensuring more effective prosecution of cybercrime-related money laundering and fostering greater judicial consistency.